Pengaruh Efektivitas Pembelajaran dan Kemandirian Belajar terhadap Hasil Belajar Mata Kuliah “Kebung Hattan” Berdasarkan Perspektif Ekonomi - Herawati, Susi; Fauziati, Popi; Yulcherlina, Yulcherlina; Gustika, Roza; Putri, Somi Nana (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study highlights  the influence of learning effectiveness and learning independence on the learning outcomes of the "Kebung Hattaan" course based on an sconomic perspective.  Bung Hatta is highly active in offering insights on economic concepts, particularly focusing on the core economic values he aims to promote, which include the value of ownership, justice, togetherness, and brotherhood. His notable economic philosophy emphasizes the people's economy, advocating for the development of the economy for farmers, fishermen, and others through cooperative efforts. The purpose of this study is to analyze the influence  of learning effectiveness and learning independence on learning outcomes. This study used 232 respondents who were randomly selected.  The collected data was processed using SPSS software and the hypothesis was proven by multiple regression. The results of the study show that the effectiveness of learning and learning independence affect student learning outcomes